Pengaruh Disiplin Kerja Dan Kompetensi Terhadap Produktivitas Kerja Pada Karyawan Bagian Produksi Pabrik Bintang Satu Kabupaten Ciamis - Ghina Sofhi Oktaviani; Mila Karmila; Barin Barlian (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine the Effect of Work Discipline and Competence on Work Productivity of employees in the production section of the Bintang Satu Factory in Ciamis Regency. This study uses a descriptive method with a quantitative approach. The research population was employees of the production section of the Bintang Satu Factory in Ciamis Regency and used a saturated sampling technique, where all members of the population were sampled, namely 40 respondents. Data collection techniques using interviews and questionnaires. The method used is multiple linear regression analysis with SPSS version 25. The results of this study indicate that Work Discipline (X1) and Competence (X2) simultaneously have a significant effect on the dependent variable, namely Work Productivity (Y). Work Discipline (X1) partially has a positive and significant effect on Work Productivity (Y). Competence (X2) partially has a positive and insignificant effect on work productivity (Y).